Distribution of Abdominal Obesity and Fitness Level in Overweight and Obese Korean Adults - Sue Kim; Ji-Young Kim; Duk-Chul Lee; Hye-Sun Lee; Ji-Won Lee; Justin Y. Jeon (International Journal of Endocrinology)
Background. Abdominal obesity and its relative distribution are known to differ in association with metabolic characteristics and cardiorespiratory fitness. This study aimed to determine an association between fitness level and abdominal adiposity in overweight and obese adults. Methods. 228 overweight and obese individuals were classified as either cardiorespiratory unfit or fit based on their recovery heart rate. Visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), the visceral-to-subcutaneous adipose tissue ratio (VAT/SAT ratio), and cardiometabolic characteristics were analyzed to examine the relationship between recovery heart rate and abdominal adiposity components. Results. After adjustments for age and sex, significant relationships of recovery heart rate and VAT, SAT, and VAT/SAT ratio were found; however, SAT was not significantly associated after further adjustment for body mass index (BMI) (r=0.045, P=0.499), whereas VAT (r=0.232, P<0.001) and VAT/SAT ratio (r=0.214, P=0.001) remained associated. Through stepwise multiple regression analyses after adjustment for age, sex, BMI, lifestyle factors, mean blood pressure, fasting glucose, HOMA-IR, lipid profiles, and hsCRP, recovery heart rate was identified as an independent variable associated with VAT (β=0.204, P<0.001) and VAT/SAT ratio (β=0.163, P=0.008) but not with SAT (β=0.097, P=0.111). Conclusions. Cardiorespiratory fitness level is independently associated with VAT and the VAT/SAT ratio but not with SAT in overweight and obese adults.